Relationship between exclusive breastfeeding and stunting among children aged 2-5 years in Indonesia - Safaah, Nurus; Yunitasari, Esti; Efendi, Ferry; Sunanita, Sunanita; Suhartono, Suhartono (Gaceta Médica de Caracas, 2022)
Introduction: Stunting is a national and global problem that needs attention. Stunting can cause growth and development problems in children. Nutrition is an aspect that is closely related to the incidence of stunting in children. This study aimed to determine the relationship between exclusive breastfeeding and the incidence of stunting in children aged 2-5 years.